A Socio Pragmatic Analysis On Directive Utterances Of Orphan Movie Manuscript - Susilowati, Dwi (2012)
This research is aimed at describing the speaker's intention, classifying and describing the linguistic forms and describing the reasons of speaker in employing the directive utterances found in ORPHAN movie manuscript. The type of this research is descriptive qualitative. The data source of this research is horror movie manuscript, ORPHAN. The technique of collecting data is documentation and the steps are reading, watching, selecting, rewriting and coding the data. The technique of analyzing data is descriptive technique. This research employs the socio pragmatics analysis for analyzing three kinds of problem statements. First, the writer uses Speech Act Theory to analyze the meaning or the speaker's intention. Second, to analyze the variants of linguistic forms is based on sintactic form, especially the types of sentences. Then, third, the writer uses SPEAKING Theory to analyze the reasons of using directive utterance. The result of this reseach finds the speaker's intentions, the linguistic forms and reasons of using directive utterances. First, for the intention of the speaker, the writer finds 38% for command, 32% for request, 20% for suggestion and 10% for warning. Second, the writer finds three types of linguistice form. The writer finds 40% in declarative sentences, 42% in imperative sentences, and 18 % in interrogative sentences. Third, to show the reason of using directive utterances, the writer finds 17% in showing anger, 19% in showing advice, 36% in showing order, 19 in showing softening utterance and 9% in showing forbide.